ANTI-TERROR ENGINEERING IN THE CASE OF POSSIBLE TERRORIST ATTACKS WITH CHEMICAL AGENTS - Biliaiev, M. M.; Berlov, O. V.; Kalashnikov, I. V.; Kozachyna, V. A. (Science and Transport Progress, 2019)
Purpose. This work aims to develop a method of local outdoor reduction of the concentration of a chemically hazardous substance, which entered the atmosphere through a cafe roof vent. It also involves the creation of a numerical model for calculating the chemical contamination zone that allows assessing the effectiveness of the screens used to minimize its level. Methodology. To solve this problem, we used the velocity potential equation that allowed to determine the air flow velocity field, and the equation of convective diffusion dispersion of a chemically hazardous agent in the atmospheric air emitted through the ventilation system in case of a terrorist attack. The simulation took into account the uneven velocity field of the wind flow, atmospheric diffusion, emission rate of a chemically hazardous agent. In the numerical integration of the velocity potential equation, we used the Liebmann method. For the numerical solution of the equation of convective diffusion dispersion of the impurity, an implicit alternate-triangular difference splitting scheme was used. Findings. The developed numerical model allowed assessing the effectiveness of building screens used to reduce the concentration of a hazardous substance and minimize the risk of toxic damage to people outdoor during an initiated emission of a chemical agent. The constructed numerical model can be implemented on computers of low and medium power, which allows it to be widely used for solving problems of the class under consideration when developing an anti-terror engineering strategy. Originality. An effective numerical model for calculating the outdoor chemical contamination zone during a possible terrorist attack using a chemical (biological) agent has been proposed. The model can also be applied to assess the effectiveness of some protective measures aimed at reducing the air pollution level during a terrorist attack. Practical value. The developed numerical model can be used to organize protective actions near social objects of a possible chemical attack by a terrorist.